Efektivitas Pengawasan Pemerintah terhadap Perizinan Tenaga Kerja Asing Menurut UU No. 13 Tahun 2003: Analisis Yuridis Normatif - Pakpahan, Elvira Fitriyani; Heriyanti; Sitompul, Mikael Jonatan (State of Islamic Institute Langsa, 2024)
Ideally, government supervision of foreign worker (TKA) permits, in accordance with Law No. 13 of 2003, should be carried out optimally to prevent violations. However, in reality, there are still many violations in the field, highlighting a gap between legal provisions and implementation. Issues arising from this gap include a lack of labor inspectors and weak coordination with relevant agencies, leading to the proliferation of illegal foreign workers. This study aims to analyze the effectiveness of TKA permit supervision from a normative juridical perspective. This article falls under the category of literature research with a qualitative approach. The methodology used is a normative legal study of labor-related regulations. The results of the study conclude that although regulations provide a strong legal foundation, the implementation of supervision in the field still needs to be improved through the enhancement of human resource capacity and inter-agency coordination to achieve the desired effectiveness.